CULTURAL CONTENT EVALUATION IN INDONESIAN INTERACTIVE ENGLISH TEXTBOOK FOR MERDEKA CURRICULUM - Jayanti, Lukitaning Nur; Ali Mustofa (ELite Journal : International Journal of Education, Language and Literature, 2023)
This research aims to analyze the cultural content in an English textbook that is customized for learning English based on Indonesian Merdeka curriculum which ideally should include a variety of traditional and regional cultures of Indonesia in its textbook. The chosen book is an authoritative book for senior-high grade entitled Bahasa Inggris untuk SMA/MA/SMK/MAK Kelas 10B by Yuniarti Dwi Arini. The objective of this research is to prove and to review the ratio of cultural content that exists within the English interaction textbook of tenth grade. Through analyzing the cultural content, it is hoped that this study is able to improve the cultural quality within other EFL textbooks in Indonesia. The research design for this study is a quantitative method, specifically, a conceptual content analysis. The coding is based upon cultural categories and cultural elements exposure of the content inside the textbook. The finding of this research shows that the percentage of cultural concepts in the analyzed object is 76%, the percentage of practice is 17%, and perspective and person's percentages are 5% and 2% respectively. For the cultural categories, there are a ratio of 55% in the target culture of English speaking country, 24% for the source culture which is from Indonesian culture, and 21% for the international target culture which is a culture that neither the target culture nor the source culture and the culture that originated in a nation that does not regard English as a first or second language.